SOFT POWER: HOW THIS GEOPOLITICAL TOOL INFLUENCES PUBLIC DIPLOMACY - Ricardo Pereira Accioly, Sérgio; Santos do Nascimento, Marielza; Pereira Nicácio, Jailton; Barbosa Diniz, Bruna; Lisboa Galvão do Nascimento, Jonathan (Revista Gênero e Interdisciplinaridade, 2025)
This article analyzes the concept of Soft Power and its role as a geopolitical tool in public diplomacy, focusing on emerging countries. In an international scenario marked by interdependence and competition for influence, Soft Power, a concept formulated by Joseph Nye (1990), stands out for its ability to attract and shape preferences without the use of force or coercion. The qualitative and exploratory approach of the research allowed us to investigate how countries, especially BRICS members, use Soft Power to strengthen their global image, building alliances and promoting international cooperation through cultural resources, values, and public policies. The overall objective of the study was to analyze how Soft Power contributes to the international projection of nations, with an emphasis on the use of cultural, political, and social elements. To achieve this objective, the study proposes to investigate the effectiveness of Soft Power in relation to Hard Power in public diplomacy and to explore the role of mega-sporting and cultural events, such as the World Cup and the Olympic Games, as strategies for image projection and strengthening of national identity. The results indicate that Soft Power is an essential tool for promoting public diplomacy and consolidating alliances based on shared values ​​and objectives. The analysis revealed that countries like Brazil and Russia have used Soft Power with different approaches and results. Brazil, through social programs and its participation in multilateral forums, has projected an image of an inclusive and cooperative nation. Russia and China, on the other hand, combine Soft Power and Hard Power resources to strengthen their influence in regional and global contexts. It was also observed that mega-sporting events, while reinforcing the image of host countries and attracting investment and tourism, can also expose political and social limitations, creating challenges for maintaining a positive image. The conclusion of this study points out that Soft Power is an effective instrument for public diplomacy, offering long-term results and facilitating co-optation and the creation of strategic alliances. However, the success of this approach depends on a balance between the projected image and the internal realities of the countries, as divergences can compromise the effectiveness of Soft Power. Gaps were identified that suggest the need for future research on the long-term impact of Soft Power, the interaction between Soft Power and Hard Power, and the relationship between Soft Power and national identity. This study contributes to the field of International Relations by highlighting Soft Power as a valuable alternative to Hard Power, especially for developing countries seeking to increase their international relevance and influence in a cooperative and sustainable manner.